2022
DOI: 10.21608/ejhc.2022.282803
|View full text |Cite
|
Sign up to set email alerts
|

Mothers' Knowledge and Practices Regarding First aids Management of Domestic Accidents among Under-Five Children in El-Beheira Governorate.

Abstract: Background: -Domestic accidents are the most common cause of death in children under 5 years of age. First aid intervention can lower the disability and increase the chances of survival of the injured child. Most of these accidents are preventable through increase mothers̛awareness and improvements in the home environment. Aim of this study to assess mothers' knowledge and practices regarding first aids management of domestic accidents among under-five children in El-Beheira governorate. Research design: a des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The knowledge of first aid management of choking hazards in the present study was high, medium, and low among 43.3, 41.3, and 15.4% of the participants, respectively. This finding is slightly higher than that reported in other surveys ( 31 , 32 ). A survey conducted by Eldosoky et al exhibited that mothers answered an average of 11 out of 29 knowledge questions correctly ( 33 ).…”
Section: Discussioncontrasting
confidence: 69%
See 1 more Smart Citation
“…The knowledge of first aid management of choking hazards in the present study was high, medium, and low among 43.3, 41.3, and 15.4% of the participants, respectively. This finding is slightly higher than that reported in other surveys ( 31 , 32 ). A survey conducted by Eldosoky et al exhibited that mothers answered an average of 11 out of 29 knowledge questions correctly ( 33 ).…”
Section: Discussioncontrasting
confidence: 69%
“…Another study conducted at Al-Khobar city in KSA revealed that 80.8% did not have knowledge about cardiopulmonary resuscitation, which is very important in handling choking ( 37 ). Concerning first aid practices for choking, Zedain et al showed that more than half of the mothers performed correct actions, such as giving mouth breathing to the child anterior fontanel, hanging a choking child upside down by the feet, or smelling the affected child perfume ( 32 ). With respect to mothers’ the practice of first aid in Qassim, KSA, 43.2% of mothers showed appropriate practice in dealing with choking ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Other authors on other continents have also shown similar results, such as Johani in Saudi Arabia, who showed that the best-educated parents and those with experience with domestic accidents involving their children had better knowledge of first-aid procedures [28]. Wani et al, also in Saudi Arabia, found the same link between the level of education and the knowledge score [30] as Zedain et al in Egypt [10].…”
Section: Factors Associated With Mothers' Knowledgesupporting
confidence: 59%
“…In Africa, studies conducted in Egypt showed that mothers' knowledge of first-aid practices regarding domestic accidents is also low. The study conducted by Gouda et al [9] revealed that 90.5% of mothers had unsatisfactory knowledge about home injuries in Egypt, and another study in Egypt showed that two-fifths of the mothers participating had fair knowledge regarding first-aid [10]. Regarding the factors associated with mothers' knowledge, African studies revealed that (i) the mother's age and the mother's education level were statistically significant independent positive predictors of higher knowledge scores [9] in Egypt, (ii) age, education, and occupation were statistically significant independent positive predictors of knowledge scores in Egypt [10], and (iii) that age, area of residence, and the level of education of the participants played a variable role regarding first-aid awareness, attitude, and knowledge in Kinshasa, Democratic Republic of Congo [11] (but this knowledge covered first-aid in general and was not focused on domestic accident in children).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation